Wordsworthian London - (re)configurations of the metropolis - Domines Veliki, Martina (2011)
In this paper we moved from the self's metaphorical inscription upon the urban scene on a September morning (J.H. Miller) through London's sense of mystery which engulfs the self as a social and intersubjective entity (Simpson) as described in Book VII of The Prelude, to The Excursion's total rejection of the life in the metropolis. We argued that the Wordsworthian concept of identity arising from a 'moral crisis' is being confirmed in his urbane 'spots of time' since all of them involve a double affirmation- negation movement. In line with the 'spatial turn' of the last decade, we further argued that the London of Wordsworth's time can be read as a complex series of different types of locations, including physical, mythological, symbolic, imagined and linguistic spaces, i.e. spaces suspended between matter and meaning (Lefaebvre). Thus the early-nineteenth-century metropolis becomes a social construct as important as time in the readings of Romantic poetry. Wordsworth's poetry dealing with the metropolis as an intersection of meanings in also an expression of the subject's oscillation between urban/natural, presence/absence, motion/stillness (J.H. Miller) and as such, it reveals the city as a complex configuration of spatiality as something indeterminate rather than something bounded and fixed.